THE EFFECT OF CURRYFLAVOR ON THE QUALITY AND CONSUMERS ACCEPTANCE OF INSTANT ANCHOVY SAGO (Stolephorussp) - Ronaldo Siagian; Syahrul Syahrul; N. Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT   This study aims to determine the effect of curry flavor on consumer acceptance of instant anchovy sago (Stolephorussp) noodles and analyze the quality of instant anchovy sago products with curry flavor produced organoleptically, microbiologically, and proximate. The method used is the experimental method, with a completely randomized Complete Design (CRD) consisting of 4 treatment levels, namely 0% (K0), 5% (K1), 7% (K2), 9% (K3). The parameters observed were organoleptic tests which included appearance, taste, texture, and aroma, and total plate number (ALT), and proximate analysis (water, ash, fat, protein, carbohydrates). The results showed that the treatment of K2 (7%) was the best treatment, towards the appearance value of 3.18 (having a rather yellowish color), a taste value of 3.08 (having a curry flavor rather strong and tastes right), texture value 3 , 01 (has a slightly brittle texture) and aroma value of 3.08 (has a distinctive curry flavor), while microbiology: total plate number (ALT) is 7.6 x 103 cells / gram with a moisture content of 10.07%, ash content of 2.81%, fat content of 0.47% and protein content of 7.59%.Keywords: Consumer acceptance, Curry seasoning, Sago noodles.